Greenhouse Gas Emission Analysis Using the Life Cycle Assessment Method for the CO2 Compressor Machine Foundation at PT Kaltim Methanol Industri - Hardianto, Rifki; Setiono; Handayani, Fajar (Sustainable Civil Building Management and Engineering Journal, 2025)
Climate change and global warming have become major global concerns due to their significant impacts on the environment and human life. One of the primary contributors to climate change is Greenhouse Gas (GHG) emissions, which are generated by various industrial activities, including the construction sector. PT Kaltim Methanol Industri, one of Indonesia's largest methanol producers, plans to add a new unit for CO₂ injection to enhance its production capacity. In this new unit, the reciprocating compressor machine foundation is a crucial structural component that must not only meet technical requirements but also consider environmental impacts, particularly GHG emissions produced during the construction process. This study employs the Life Cycle Assessment (LCA) method to identify the life cycle stages that contribute the most to GHG emissions and to compare the GHG emissions of various foundation types, namely standard block foundation, spring-supported foundation types 1, 2, and 3. The dimensions of each foundation type are 10.2 m in length and 6.2 m in width, with varying heights: standard block foundation (1.5 m), spring-supported type 1 (1.25 m), spring-supported type 2 (1.0 m), and spring-supported type 3 (0.75 m). The height above ground for each foundation type is 0.35 m. The study results indicate that the raw material stage contributes the most emissions, with the highest emissions recorded in the standard block foundation at 65,969.8476 kgCO₂e. Meanwhile, the foundation with the lowest emissions is the spring-supported type 3, producing 36,550.0597 kgCO₂e.